MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MERONCE PADA ANAK USIA 4-5 TAHUN DI PAUD AS-SAKINAH DESA SUNGAI JALAU KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Suhartini, Suhartini; Zulkifli, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The study aims to see an increase in fine motor skill on the group A through meronce activity in early childhood As-Sakinah the Village Sungai Jalau district Kampar northern regency of Kampar. The study the kind of research using research a class action or PTK which was held in two cycle. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children in group A numbering 15 children in early childhood As-Sakinah. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. the research showed that activities meronce can improve fine motor skills in children in group A. It can be seen from the increase in the average percentage of fine motor skills in the first cycle of 54.11% which is the criterion begins to develop (MB) and an increase of 51.54% in the second cycle be 82.00% which is very good at developing criteria (BSB). Thus, the activities meronce can improve fine motor skills children aged 4-5 years in early childhood As-Sakinah the Village Sungai Jaluau Districk Kampar North regency of Kampar.Keywords : Fine Motor Skill, Activity Meronce